Water quality assessment for aquaculture using deep neural network - Rajeshwarrao Arabelli; T. Bernatin; Venkataramana Veeramsetty (Desalination and Water Treatment)
Aquaculture is one of the promising sector for the economic growth of developing countries like India. Exporting of fish based foods increasing gradually that raises Gross Domestic Product (GDP) values of country. In this type of scenarios, it is very essential to take care of quality of fish ponds water for the growth of fish species and metabolism. In this paper, optimal DNN model is developed by tuning the various parameters like number of hidden layers, hidden neurons and activation functions using Python programme in visual studio. A new dataset is generated with 1400 excellent quality water samples, 1400 good quality water samples and 1500 poor quality water samples. This dataset consists of total 14 input parameters like temperature, turbidity, dissolved Oxygen, biochemical oxygen demand (BOD), CO2, pH, alkalinity, hardness, calcium, ammonia, nitrite, phosphorus, H2S and plankton. The proposed model is validated by comparing with other machine learning models like support vector machine, K-Nearest Neighbour and Naive Bayes classifier in terms of metrics like accuracy, f1-score, precision and recall. The proposed DNN model that has training accuracy 97.41% and testing accuracy 95.69% is used to deploy in back-end of web application to assess the quality of water in fish ponds.